If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+5+x=2(3x-3)
We simplify the equation to the form, which is simple to understand
2x+5+x=2(3x-3)
Reorder the terms in parentheses
2x+5+x=+(+6x-6)
Remove unnecessary parentheses
+2x+5+x=+6x-6
We move all terms containing x to the left and all other terms to the right.
+2x+1x-6x=-6-5
We simplify left and right side of the equation.
-3x=-11
We divide both sides of the equation by -3 to get x.
x=3.6666666666667
| a(a-8)=17-a | | 27=-5(b-2)+5(b+4) | | 8x-161=5x+73 | | 4x+6+7x=34+7 | | 4x^2+4x-5=2x(x+3-1) | | x-5.3=10.7 | | 72y^16-9y^3=0 | | 2x+24=144 | | x+3.8=5.4 | | -4+c+7=-12 | | 54=a-22 | | -3(v+8)=-6 | | 7x^2+9x-18=0 | | 8(x+1)-8(3+8x)=-16 | | (K+3)(7k+3)=0 | | 6*(9x+2)=35 | | .25-.6*y=.75-.3*y | | 4.85x-7x=-3.655 | | f(n)=2n-4 | | 6x^2+7x-6=0 | | 18x+30=-150 | | 16m+14=10m+16 | | 3x+x-36+4x=180 | | .5(a*6)=.3*a | | 16+4+18x=180 | | 11x-(4x-6)=62 | | j+13=-3 | | -60=-3(4+6n)+2(5n+4) | | F(v-2)=6x+7 | | 3+n=-7 | | X^2-9y^2+2x-54y-98=0 | | 7+k=42 |